2019
DOI: 10.1002/jia2.25244
|View full text |Cite
|
Sign up to set email alerts
|

HIV self‐testing: breaking the barriers to uptake of testing among men and adolescents in sub‐Saharan Africa, experiences from STAR demonstration projects in Malawi, Zambia and Zimbabwe

Abstract: Introduction Social, structural and systems barriers inhibit uptake of HIV testing. HIV self‐testing ( HIVST ) has shown promising uptake by otherwise underserved priority groups including men, young people and first‐time testers. Here, we use characteristics of HIVST kit recipients to investigate delivery to these priority groups during HIVST scale‐up in three Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
120
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 24 publications
9
120
1
Order By: Relevance
“…Although we cannot define exact usage, participants receiving kits through community-based distributors were asked to return their used kits with a self-administered questionnaire. Use was confirmed by inspection of used kits for 75.7% of 27,789 distributed kits in HitTB (Study 1, Table 2) and 53.2% of 163,300 kits distributed under STAR-GP in Malawi [52] including 137,915 kits for which we report SHs (Studies 9 and 11, Table 2) [4,6,52]. Thus, while non-use of distributed kits will be contributing to underestimation of SHs, this has relatively little impact on our SH frequency-estimates reported here.…”
Section: Prism: 19-year-old Hiv-negative Wife In Discordant Relationshipmentioning
confidence: 87%
“…Although we cannot define exact usage, participants receiving kits through community-based distributors were asked to return their used kits with a self-administered questionnaire. Use was confirmed by inspection of used kits for 75.7% of 27,789 distributed kits in HitTB (Study 1, Table 2) and 53.2% of 163,300 kits distributed under STAR-GP in Malawi [52] including 137,915 kits for which we report SHs (Studies 9 and 11, Table 2) [4,6,52]. Thus, while non-use of distributed kits will be contributing to underestimation of SHs, this has relatively little impact on our SH frequency-estimates reported here.…”
Section: Prism: 19-year-old Hiv-negative Wife In Discordant Relationshipmentioning
confidence: 87%
“…Also in this Supplement , Hatzold et al . reviewed STAR data from Malawi, Zambia and Zimbabwe that assessed the integration of HIVST tools into HIV programming . They found that by having clients perform HIVST in outpatient settings, they were able to decongest clinical testing facilities because healthcare workers could focus only on those that screened positive.…”
mentioning
confidence: 99%
“…They found that by having clients perform HIVST in outpatient settings, they were able to decongest clinical testing facilities because healthcare workers could focus only on those that screened positive. They also demonstrated the ability to reach men through community distribution and in particular workplaces, and explored male attitudes to HIVST, noting that the briefer counselling messages, privacy and convenience appealed to them .…”
mentioning
confidence: 99%
“…An HIVST scale-up study conducted in these three African countries revealed promising results. A higher proportion of male self-testers (22.3%), compared with women (17.1%), were first-time testers, which was apparent in Zimbabwe (16.2% vs. 11.4%), Zambia (25.4 vs. 17.7%), and Malawi (27.9 vs. 25.9%) [22]. Several other different scholars have shown HIVST as an acceptable strategy to improve men's uptake of HTSs [16,[24][25][26].…”
Section: Introductionmentioning
confidence: 94%
“…The World Health Organization (WHO) published the first global guidelines on HIV self-testing (HIVST) in 2016 [17]-an intervention that has shown global potential to increase uptake of HTSs [13,[18][19][20][21]. Studies have reported success, with HIVST being offered to men in health care facility-based settings [22,23] and community settings [22], in Malawi, Zambia, and Zimbabwe. An HIVST scale-up study conducted in these three African countries revealed promising results.…”
Section: Introductionmentioning
confidence: 99%